Collectively Facilitated Behavior of the Neonate Caterpillars of Cactoblastis cactorum (Lepidoptera: Pyralidae) - Fitzgerald, Terrence D. (MDPI, 2016)
The behavioral biology of the first instar larva of Cactoblastis cactorum was studied from the time of eclosion until the colony penetrated and initiated excavation of the host plant. Hatching from an egg stick was asynchronous, requiring 20 h for the entire cohort to eclose at 50%–70% RH and significantly longer at a lower range of RHs. On eclosion, neonates aggregated in an arena at the base of their egg stick and did not attempt to excavate the cladode until an average of 25 caterpillars had collected, approximately 15 h after the onset of egg hatch. Typically only a single entrance hole was formed, limiting the active process of excavating to one or a few individuals at-a-time until the host was fully penetrated and enlarged internally. Olfactometer tests showed that the neonates are strongly attracted to volatile chemicals released when caterpillars chewed into the cladode, accounting for the strong fidelity of the whole cohort to the initial site of penetration. In one instance, the caterpillars were observed to deal with an explosive release of mucilage by imbibing the liquid until the flooded zone was drained and the caterpillars could reenter the plant through the original entrance hole. Once inside the cladode, marked individuals adopted a regular cycle of defecating at the surface at a mean interval of approximately 10 min when followed for 35 successive cycles. Blanket spraying cladodes with a mandibular gland extract prior to hatching led to the independent dispersal of neonates and a failure to form an arena. When the cladode was impenetrable at the site of eclosion, the active cohort of unfed neonates set off together in search of a new site, marking and following a persistent trail that allowed late-to-eclose caterpillars to join their departed siblings. The adaptive significance of these observations is discussed in the context of the life history of the caterpillar.